2009
DOI: 10.1152/ajplung.90507.2008
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection alters surfactant protein A expression in human pulmonary epithelial cells by reducing translation efficiency

Abstract: , a collectin that is an important component of the pulmonary innate immune system. SP-A binds to the virus, targeting the infectious agent for clearance by host defense mechanisms. We have previously shown that while the steady-state level of SP-A mRNA increases approximately threefold after RSV infection, steady-state levels of cellular and secreted SP-A protein decrease 40 -60% in human type II cells in primary culture, suggesting a mechanism where the virus alters components of the innate immune response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 62 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…The opposite effect was found when this sequence element was deleted from the variants where it naturally occurs, i.e., 6A 2 , and all SFTPA2 variants (1A, 1A 0 , 1A1, 1A 2 , 1A 3 , and 1A 5 ). Together, these results indicate that the SP-A 11-nt element has a negative effect on gene expression under normal conditions and are consistent with our previous work where variants 6A 2 , 6A 3 , 6A 4 , and their corresponding mutants were studied for their impact of this element on translation and mRNA stability (60).…”
Section: Sftpa1 and Sftpa2 3=utrs Affected Reporter Expression With Vsupporting
confidence: 92%
See 3 more Smart Citations
“…The opposite effect was found when this sequence element was deleted from the variants where it naturally occurs, i.e., 6A 2 , and all SFTPA2 variants (1A, 1A 0 , 1A1, 1A 2 , 1A 3 , and 1A 5 ). Together, these results indicate that the SP-A 11-nt element has a negative effect on gene expression under normal conditions and are consistent with our previous work where variants 6A 2 , 6A 3 , 6A 4 , and their corresponding mutants were studied for their impact of this element on translation and mRNA stability (60).…”
Section: Sftpa1 and Sftpa2 3=utrs Affected Reporter Expression With Vsupporting
confidence: 92%
“…Reporter constructs were transfected in NCI-H441 cells in the presence or absence of miRNA mimics, and reporter gene expression was analyzed. We found that human miRNA mir-767 negatively affected expression of constructs containing SFTPA1 and SFTPA2 variants, whereas mir-4507 affected only constructs with 3=UTRs of SFTPA1 variants 6A, 6A 3 , and 6A 4 (not containing the 11-nt element). Three miRNAs (mir-183, mir-449b, and mir-612) inhibited expression of recombinants of SFTPA2 variants and the SFTPA1 variant 6A 2 , all containing the 11-nt element.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…H441 cells have also been evaluated as models of the peripheral lung. These cells, which were derived from a papillary adenocarcinoma of the lung, have features characteristic of Club cells (Gazdar et al, 1990) and have been used as a model of bronchiolar epithelium (Bruce et al, 2009). However, more recently, it has been found that culture of H441 cells on semi-permeable filter supports results in formation of electrically tight monolayers (peak TEER values of approximately 1000 Ω cm 2 after 8-12 days in culture) which are able to differentiate paracellularly transported substrates according to their molecular weight (Salomon et al, 2014).…”
Section: Cfdeo-/6rep-cftrmentioning
confidence: 99%